1999
DOI: 10.1108/08858629910254076
|View full text |Cite
|
Sign up to set email alerts
|

On achieving exoneration after a product safety industrial crisis

Abstract: Deals with the management of industrial crises, low-probability, high-impact events which typically affect companies involved in them, negatively. Specifically examines the role of three important factors, i.e. company's reputation, the organizational response that it selects to adopt in order to deal with the crisis, and external effects that are faced during a product safety crisis. Emphasis is placed on determining the effects of an industrial crisis (caused by a harmful product) on the consumers' attributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 19 publications
(19 reference statements)
5
55
0
4
Order By: Relevance
“…However, compliance will avoid increasing attributions of blame towards the company. These findings are consistent with evidence that negative news bears far more weight than positive news (Dean [63]). …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…However, compliance will avoid increasing attributions of blame towards the company. These findings are consistent with evidence that negative news bears far more weight than positive news (Dean [63]). …”
Section: Resultssupporting
confidence: 88%
“…Knowledge about the company's brand as well as goodwill affect the consumer attitude towards brand (Mowen et al, [48]; Siomkos and Kurzbard, [9]; Dean, [63]; Siomkos and Shrivartara, [50]; Dawar and Lei, [4]), the consumer's brand loyalty during PHC (Cleeren et al, [56]), external factors role in product harm-crisis (Siomkos and Kurzbard, [9] [73]), pre-crisis category advertising and usage (Cleeren et al, [56]), the role of CSR (Klein and Dawar, [57]; Matos and Rossi, [6]), safety measures on the defective products (Griffin et al, [58]), before defects, product recall approach (Matos and Rossi, [6]), and customer's prior perceptions (Dawar and Pillutla, [3]). …”
Section: Product Harm Crisismentioning
confidence: 99%
“…Consumers' attitudes are the most important indicator for measuring the effectiveness of crisis management [25]. Effective crisis management involves the consumer's approval of the organizational response and consumer's persuasion that the product is safe again as the company has overcome the crisis [26].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In involuntary recall, a company takes action only after an agency ' s intervention. Siomkos 28 defi nes involuntary recall as ' simple compliance with the minimum legal requirements ' . Voluntary recall includes the disclosure of information regarding the crisis and the recalling of the product before an agency ' s order.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have shown that a company ' s reputation signifi cantly affects the degree to which a company is successful in dealing with the crisis. 16,19,28 Siomkos 28 concluded that companies involved in a crisis are more likely to be held responsible for the defective product if they have a poor reputation. More specifi cally, it has been shown that a highly respected and well-known company is regarded more favourably in cases of product recalls.…”
Section: Introductionmentioning
confidence: 99%